Effect of Temperature on the Stability and Release Profile of Ibuprofen Microcapsules - Issraa R. Abed Al- Rahman (College of Pharmacy University of Baghdad, 2017)
The stability and releasing profile of 2:1 core: wall ratio ibuprofen microcapsules prepared by aqueous coacervation (gelatin and acacia polymers coat) and an organic coacervation methods (ethyl cellulose and sodium alginate polymers coat) in weight equivalent to 300mg drug, were studied using different storage temperatures 40°C, 50°C ,60°C and refrigerator temperature 4°C in an opened and closed container for three months (releasing profile) and four months (stability study).It was found that, these ibuprofen microcapsules were stable with expiration dates of 4.1 and 3.1 years for aqueous and an organic method respectively.Aqueous prepared ibuprofen microcapsules were found more stable than those microcapsules prepared by organic method with activation energy (Ea) 4804.8 cal/mol and 5033.6 cal/mol of a drug respectively.The releasing percentage of ibuprofen for all microcapsules prepared by both methods was decreased as the storage temperatures increased, except for microcapsules prepared by aqueous method, which were found to be the same at 25-40°C as the standard one which stored at 25°C temperature, on the other hand , as the temperature decreased to 4°C (refrigerator ) of an open and closed container ,the amount of drug detected in microparticles is increased. These differences in the amount of drug released may be referred to the change in physical properties in polymer coats or in the amount of drug detected in a whole microcapsules. Keyword: Ibuprofen Microcapsules, Storage Temperature, Stability.